The risks of acute exposure to black carbon in Southern Europe: results from the MED-PARTICLES project. Issue 2 (10th November 2014) - Ostro, Bart; Tobias, Aurelio; Karanasiou, Angeliki; Samoli, Evangelia; Querol, Xavier; Rodopoulou, Sophia; Basagaña, Xavier; Eleftheriadis, Kostas; Diapouli, Evangelia; Vratolis, Stergios; Jacquemin, Benedicte; Katsouyanni, Klea; et al.
Abstract : Objectives: While several studies have reported associations of daily exposures to PM2.5 (particles less than 2.5 µm) with mortality, few studies have examined the impact of its constituents such as black carbon (BC), which is also a significant contributor to global climate change. Methods: We assessed the association between daily concentrations of BC and total, cardiovascular and respiratory mortality in two southern Mediterranean cities. Daily averages of BC were collected for 2 years in Barcelona, Spain and Athens, Greece. We used case-crossover analysis and examined single and cumulative lags up to 3 days. Results: We observed associations between BC and all mortality measures. For a 3-day moving average, cardiovascular mortality increased by 4.5% (95% CI 0.7 to 8.5) and 2.0% (95% CI 0 to 4.0) for an interquartile change in BC in Athens and Barcelona, respectively. Considerably higher effects for respiratory mortality and for those above age 65 were observed. In addition, BC exhibited much greater toxicity per microgram than generic PM2.5. Conclusions: Our findings suggest that BC, derived in western industrialised nations primarily from diesel engines and biomass burning, poses a significant burden to public health, particularly in European cities with high-traffic density.